Illegal Streaming Sites: Legal Analysis and Challenges in the Digital Era - Anggo Doyoharjo; FX. Hastowo Broto Laksito (Lembaga Pengembangan Kinerja Dosen, 2025)
Illegal streaming sites are one of the forms of copyright infringement that are rampant in the digital era and have a significant impact on the creative industry, the economy, and law enforcement. This research analyzes the Indonesian legal framework consisting of Law No. 28 of 2014 on Copyright, Law No. 11 of 2008 jo. Law No. 19 of 2016 on Electronic Information and Transactions, as well as the technical regulations of the Ministry of Communication and Information (Kominfo) in addressing these violations. The findings indicate that although the legal framework is in place, enforcement still faces technical, legal, social, and complex cross-border challenges. These sites often utilize foreign servers, mirror domains, and anti-blocking technology to evade blocking, thus requiring international cooperation thru mechanisms such as Mutual Legal Assistance (MLA) and coordination with the World Intellectual Property Organization (WIPO). An effective counter-strategy must be multidimensional, encompassing regulatory strengthening, the use of detection technologies such as digital watermarking and content ID systems, as well as public education to curb the demand for illegal content. A comparison with the United States, Japan, and South Korea shows that proactive enforcement, a quick notice-and-takedown mechanism, and industry cooperation have proven effective in reducing violations. In conclusion, the eradication of illegal streaming sites in Indonesia requires continuous synergy between the government, industry, and society to protect copyright and the sustainability of the creative industry ecosystem in the digital era.